A complementary list of bird species for Pu Mat national park, Nghe An province and North central Vietnam - Tuong, Ngo Xuan; Thuy, Le Dinh (Academia Journal of Biology, 2012)
A total of 325 bird species belonging to 45 families, 177 genera of 15 orders were recorded in Pu Mat National Park, Nghe An province. Up to 2011, the total number of bird species recorded in the park currently comprise 36.64% of the bird fauna of Vietnam. Among 325 bird species recorded in Pu Mat National Park, 22 species (6.77% of total bird species of Pu Mat National park) are new to the park, and 85 species are new to the North region of Central Vietnam in comparison with the species composition in the "List of birds of Vietnam" compiled by Vo Quy, Nguyen Cu (1995) and Nguyen Lan Hung Son, Nguyen Thanh Van (2011).